2013
DOI: 10.1016/j.bjane.2012.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Hyperthermia in Brazil: Analysis of Hotline Activity in 2009

Abstract: The number of calls per year in the Brazilian hotline service for MH is still low. The characteristics of MH episode were similar to those reported in other countries. The knowledge of MH in Brazil needs to be increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 17 publications
1
9
0
2
Order By: Relevance
“…The service concluded that the number of calls is still low and it is necessary to increase the knowledge about MH in Brazil. (5) The results of this study showing that health professionals had little knowledge of the subject of MH are in agreement with those presented in other studies (5, 9,-10) , emphasizing the need for training and expanding the knowledge of health professionals to enable them to recognize patients who may present a crisis of MH during the perioperative period.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The service concluded that the number of calls is still low and it is necessary to increase the knowledge about MH in Brazil. (5) The results of this study showing that health professionals had little knowledge of the subject of MH are in agreement with those presented in other studies (5, 9,-10) , emphasizing the need for training and expanding the knowledge of health professionals to enable them to recognize patients who may present a crisis of MH during the perioperative period.…”
Section: Discussionsupporting
confidence: 91%
“…(4) In Brazil, there are no current data on the incidence; however, it is estimated that general anesthesia is performed approximately fi ve million times annually, and therefore this number is consistent with the annual incidence of 500 to 1,000 cases of MH in São Paulo alone. (5) Clinical signs that may indicate the onset of MH are: unexplained tachyarrhythmias, which may occur in 96% of cases; tachypnea in 85% of patients; and acidosis in 80% of patients in response to increased gluconeogenesis. An event will also produce abnormal amounts of lactic acid, carbon dioxide (CO 2 ), and heat, as well as sustained contraction of muscle groups, which leads to greater use of available adenosine triphosphate (ATP) and oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…Malignant hyperthermia was first described in 1960 and occurs in a frequency up to 1:10,000 of general anesthesia in children and 1:50,000 of general anesthesia in adults (1) . The first report of malignant hyperthermia in Brazil was published in 1975 during anesthesia with halothane, but there are no data on its real incidence in Brazil (2) . The treatment consists of early recognition of triggering agents, removal of these agents and administration of Dantrolen.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment consists of early recognition of triggering agents, removal of these agents and administration of Dantrolen. Malignant hyperthermia is an anesthetic emergency and there are protocols with explicit roles for each team member which should be standardized and oriented toward effective care (2) . General anesthesia is a reversible state of unconsciousness that allows patients to undergo surgical procedures in a safe and humane way.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation